Integrating Design Thinking in Teaching High School Physics - Cañada, Markpoalo; Cubero, Kenny James; Del Agua, Queennie; Gerona, Rizza Nikka; Libres, Dominic; Ligue, Resel; Mauring , Jonathan Jr; Padilla, Hans Adam; Quiña, John Paul; Ramos, Rochin; Ramos, Ofelia Aljade (Journal of Interdisciplinary Perspectives, 2025)
This study examined the implementation of Design Thinking (DT) in teaching high school physics through a comprehensive two-day seminar workshop. A mixed methods approach was employed to assess its effectiveness, combining quantitative and qualitative data collection and analysis. The study involved 21 pre-service teachers (PSTs) majoring in General Science from a state university in Cebu City, Cebu. The DT Framework, which comprised the following phases: Empathy, Define, Ideate, Prototype, and Test, guided the PSTs in demonstrating their teaching strategies, with the researchers evaluating their performance at each stage. Findings indicate that the Empathy phase was strengthened by effective pre-interviews, role assignments, resource availability, and structured organization. In the Define phase, PSTs successfully facilitated problem identification and encountered difficulties in guiding learners to translate questions into actionable insights. The Ideate phase encouraged creativity and collaboration, yet PSTs struggled to clarify the distinction between originality and novelty. During the Prototype phase, they promoted adaptability and resourcefulness but lacked a clear timeline for task completion. Finally, in the Test phase, while PSTs emphasized iterative improvement, they did not provide a rubric for design assessment or a structured approach to gathering end-user feedback. Overall, PSTs expressed high satisfaction with the workshop, praising the topic's relevance, the presenters' expertise, and the engaging activities. Despite these successes, recommendations include refining feedback mechanisms and incorporating a broader range of activities to enhance future workshops. This study highlights the potential of DT in enriching physics education and focuses on areas for further refinement in teacher training programs.